MAKNA SIMBOLIK KOMUNIKASI BUDAYA DALAM TRADISI KAOMBO TEI PADA MASYARAKAT DESA WAJOGU KECAMATAN LAKUDO KABUPATEN BUTON TENGAH - Zulfikar; Harry Fajar Maulana; Muh. Hidayatullah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the symbolic meaning of cultural communication in the Kaombo Tei tradition practiced by the community of Wajogu Village, Lakudo District, Central Buton Regency. The Kaombo Tei tradition is a community-based local mechanism for managing water resources through a traditional institution. This research employs a qualitative method to understand the phenomenon from the participants’ perspective, as well as its social and institutional context. The findings show that Kaombo Tei involves several traditional rituals such as hair cutting (alano wulu focu), sea bathing, and the use of eggs as symbols of physical and spiritual purification. This tradition functions to maintain the sustainability of marine resources through an open and closed water system governed by customary rules that prohibit fishing activities during certain periods. The ritual is believed to carry spiritual and social consequences, thereby strengthening community compliance with these customary regulations. The symbolic meanings embedded in this tradition include cleansing oneself from negative elements through the egg symbol, relieving anxiety through hair-cutting rituals, and protection from harm through sea bathing. The Kaombo Tei tradition is conducted twice a year, following seasonal changes, and has been shown to have positive impacts on the preservation of aquatic environments and the balance of the local ecosystem.